2019
DOI: 10.1016/j.joca.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Muscle size and composition in people with articular hip pathology: a systematic review with meta-analysis

Abstract: s u m m a r yObjective: To synthesise and evaluate the current evidence investigating muscle size and composition in non-inflammatory articular hip pathology. Methods: A systematic review of five electronic databases, using three concepts; articular hip pathology (e.g., osteoarthritis (OA)); hip muscles; and outcomes (e.g., muscle size and adiposity) was undertaken. Studies addressing non-inflammatory or non-traumatic articular hip pain, using measures of muscle size and adiposity were included and appraised f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 57 publications
0
29
1
Order By: Relevance
“…Akin to current findings, Zacharias et al (2016) reported GMax, GMed, and GMin muscle atrophy as well as increased levels of fatty infiltration in GMax and GMin. However, a recent systematic review and meta-analysis on muscle size and composition in people with articular hip pathology reported the variability in magnitude of difference in hip muscle size between people with hip pathology and those without (Lawrenson et al, 2019). The pattern of muscle atrophy reported in this study is not consistent across all hip conditions.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Akin to current findings, Zacharias et al (2016) reported GMax, GMed, and GMin muscle atrophy as well as increased levels of fatty infiltration in GMax and GMin. However, a recent systematic review and meta-analysis on muscle size and composition in people with articular hip pathology reported the variability in magnitude of difference in hip muscle size between people with hip pathology and those without (Lawrenson et al, 2019). The pattern of muscle atrophy reported in this study is not consistent across all hip conditions.…”
Section: Discussioncontrasting
confidence: 86%
“…Further, it is difficult to know whether the increase in size of these muscles combined, is due to active contractile tissue, or noncontractile tissue (e.g., fat infiltration). For these reasons, as suggested in a recent systematic review, consideration of individual muscle size and quality (e.g., fat infiltration) in future research is recommended (Lawrenson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Imaging findings related to the pain of hip osteoarthritis include the intramedullary intensity changes in the acetabulum or femoral head on magnetic resonance imaging (MRI), 1 - 4 so-called bone marrow lesions (BMLs), and muscle atrophy around the hip joint. 5 - 7 A comprehensive scoring system of MRI findings in hip osteoarthritis, the Hip Osteoarthritis MRI Scoring System (HOAMS), has also been established. 1 , 8 However, the HOAMS is very complicated, and it takes time to evaluate and score all findings.…”
Section: Introductionmentioning
confidence: 99%
“…LDD has been reported to be related to GTPS 34,35) , and GMedS is also accompanied by low back pain and some symptoms of LDD are possibly attributed to GMedS. Numerous reports have pointed out that hip osteoarthritis is related to GTPS or decreased GMed strength [36][37][38][39][40] . Thus, some symptoms of hip osteoarthritis can be possibly attributed to GMedS.…”
Section: Introductionmentioning
confidence: 99%